Sustainable production of radionuclidically pure antimony-119 - Aeli P. Olson; Francesca A. Verich; Paul A. Ellison; Eduardo Aluicio-Sarduy; Robert J. Nickles; Jason C. Mixdorf; Todd E. Barnhart; Jonathan W. Engle (SpringerOpen, 2024)
Abstract Background Radiopharmaceutical therapy (RPT) uses radionuclides that decay via one of three therapeutically relevant decay modes (alpha, beta, and internal conversion (IC) / Auger electron (AE) emission) to deliver short range, highly damaging radiation inside of diseased cells, maintaining localized dose distribution and sparing healthy cells. Antimony-119 (119Sb, t1/2 = 38.19 h, EC = 100%) is one such IC/AE emitting radionuclide, previously limited to in silico computational investigation due to barriers in production, chemical separation, and chelation. A theranostic (therapeutic/diagnostic) pair can be formed with 119Sb's radioisotopic imaging analogue 117Sb (t1/2 = 2.80 h, Eγ = 158.6 keV, Iγ = 85.9%, β+ = 262.4 keV, Iβ+ = 1.81%). Results Within, we report techniques for sustainable and cost-effective production of pre-clinical quality and quantity, radionuclidically pure 119Sb and 117Sb, novel low energy photon measurement techniques for 119Sb activity determination, and physical yields for various tin target isotopic enrichments and thicknesses using (p, n) and (d, n) nuclear reactions. Additionally, we present a two-column separation providing a radioantimony yield of 73.1% ± 6.9% (N = 3) and tin separation factor of (6.8 ± 5.5) x 105 (N = 3). Apparent molar activity measurements for deuteron produced 117Sb using the chelator TREN-CAM were measured at 42.4 ± 25 MBq 117Sb/µmol (1.14 ± 0.68 mCi/µmol), and we recovered enriched 119Sn target material at a recycling efficiency of 80.2% ± 5.5% (N = 6) with losses of 11.6 mg ± 0.8 mg (N = 6) per production. Conclusion We report significant steps in overcoming barriers in 119Sb production, chemical isolation and purification, enriched target material recycling, and chelation, helping promote accessibility and application of this promising therapeutic radionuclide. We describe a method for 119Sb activity measurement using its low energy gamma (23.87 keV), negating the need for attenuation correction. Finally, we report the largest yet-measured 119Sb production yields using proton and deuteron irradiation of natural and enriched targets and radioisotopic purity > 99.8% at end of purification.